Pengaruh Pemberian Bahan Organik Cair Asal Kulit Pisang dan Air Cucian Beras terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pre-nursery - Ariyanti, Mira; Meidya Adhani, Rafika; Ratna Dewi Anjarsari, Intan; Rosniawaty, Santi (Pusat Penelitian Kelapa Sawit, 2023)
Excessive use of inorganic fertilizers in oil palm nurseries can be minimized by using liquid organic ingredients. The use of liquid organic ingredients (LOI) from banana peels and rice washing water aimed to determine and study its effect on the growth of oil palm seedlings in pre-nursery. The experiment was carried out at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University, in February - May 2022. The experiment used a randomized block design (RBD) with nine treatment combinations and was repeated three times, each treatment consisting of two seeds. The treatments tested were control without the addition of liquid organic ingredients from banana peels and rice washing water, as well as a combination of various doses of LOI from banana peels and rice washing water. The experimental results showed that the LOI and rice washing water given only had a significant effect on the leaf area of oil palm seedlings at 1 MAT and leaf chlorophyll content at 3 MAT. However, it was seen that giving 25 mL LOI from banana peel/L water/plant combined with 250 mL of rice washing water has a good influence on the growth of oil palm seedlings in the pre-nursery.